بنية الحجاج في الخطاب القرآني : آيات الدعاء أنموذجاً - فاضل، إسراء سلمان محمد (2015)
The study tackles the verses of prayer in the light of the theory of argument as language is essentially and functionally argumentive. The study first defines the concept of argument, in old and modern times, and how the term was developed in modern linguistic. Chapter One reveals the role of associations and argumental factors in discourse and their role in directing the saying in the process of associating the arguments and the results. Chapter Two reveals the argument techniques and their role according to (Pearlman) and their dimension. The Chapter investigates the role of speech act in the process of directing the speech to performative level, and the role of figurative methods in creating the effect redener the recipient into argument. Chapter Three investigates two important issues in the argumentive lesson which are (the argumentive ladder) and their role in the arrangement of the arguments reaching to the persuasion, and (exigency) which is a condition to know the role of each of them in drawing of the picture of the exigency argument that would be conveyed to the recipient and the accompanying the excitement. The study was concluded with the most important findings and the thesis ends with a list of the references and resources.